The Submerged Scope of the Spanish Flu: Negotiating Representational Challenges in Willa Cathers One of Ours - Sharmistha Das (Global Journal of Human-Social Science, 2023)
The pandemic of 1918 or more famously the Spanish flu remains a dark and disruptive phenomenon a scourge in the face of time and history But what makes it most intriguing is its own oxymoronic entity-its own absent-presence an experience that was simultaneously ubiquitous and hidden Such exclusion when understood as deliberate remains at the heart of discourses of power and domination Human civilization is rife with many such practices be it indiscriminate exploitation of the environment or the discrimination on grounds of race caste colour gender sexuality et al- all based on a systemic delegitimization of discarded negatives Butler Representation when empowered with a disruptive force that can push through state sanctioned borders and mainstream interpretive constructs can emerge as alternative frames that can see through the suppressed Lifting the veil of the archival dust ambient upon long forgotten stories will enable us to excavate narrative possibilities from all that has been silenced granting them a voice that is long due This article will be structured into two cluster of materials the first part will briefly document the extent and spread of the contagion tracing its evolution from a miasmic atmospheric entity shifting in waves towards becoming a horrifying visible reality